"Slava Ukraini!" Strategy and the Spirit of Ukrainian Resistance 2014-2023 - Käihkö, Ilmari (Helsinki University Press, 2023)
"Slava Ukraini!" Strategy and the Spirit of Ukrainian Resistance tells the story of the volunteers lauded to have saved Ukraine twice. The volunteers first emerged in the spring of 2014 after the onset of the war in Donbas in a context characterized by ambiguity, state weakness, political uncertainty, and threat. They re-emerged again in February 2022 after the large-scale Russian invasion. Aimed at an interdisciplinary audience, this volume makes significant contributions to our understanding of events in Ukraine over the past decade. Based on ethnographic fieldwork with volunteer battalion fighters, the volume focuses on strategy, or the creation, control, and use of force. This framework is first applied to the volunteer militias to further the understanding of militia strategy conducted after 2014, and then to the first year and a half that followed the Russian invasion in 2022. "Slava Ukraini!" also discusses the long-term sociological impact of volunteer battalions and the war they fought in Ukraine. The Ukrainian spirit of resistance emerged first on the Maidan in November 2013, ignited the volunteer Spirit of 2014 after the Russian invasion and annexation of Crimea, and ultimately flared-up on a national scale in a manner which surprised the invading Russian forces in 2022. Yet initially the volunteers may also have exacerbated internal divisions in Ukraine. The Spirit of 2014 was also better suited to a war of movement than immobile trench warfare that left little room for heroism and aggressive soldiering. Unrealistic expectations about modern warfare led to disillusionment, and many volunteers leaving the war in 2015. The perceived stalemate and lack of Ukrainian soldiers by late 2023 raised the question of a similar dynamic witnessed in 2014 and 1914 alike.